2011
DOI: 10.1029/2010ja015807
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the power transferred from satellite-magnetosphere interactions to auroral emissions

Abstract: [1] Io's interaction with the Jovian magnetosphere generates a power of about 10 12 W which propagates as Alfvén waves along the magnetic field lines and is partly transferred to electrons, resulting in intense auroral emissions. A recent study of the power transmission along the Io flux tube and of the electron acceleration at high latitudes showed that the power of the observed emissions is well explained by assuming filamentation of the Alfvén waves in the torus and the acceleration of the electrons at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 53 publications
10
52
0
Order By: Relevance
“…The power transferred to the electrons by an Alfvén wave packet can be estimated by assuming that, for each Alfvén wavelength, the electrons are accelerated by the Alfvén wave parallel electric field during a half‐period of the wave. Hess et al [2010, 2011b] showed that in this case, an Alfvén wave packet carrying a power P w transfers to the electrons a power P e given by: where a ( k ) is the phase velocity of a Alfvén wave packet component with a wavenumber k in the equatorial plane (and perpendicular wavenumber ). The electrons to be accelerated are described by a thermal velocity v th and an inertial length λ e .…”
Section: Generation Of Hot Electronsmentioning
confidence: 99%
See 1 more Smart Citation
“…The power transferred to the electrons by an Alfvén wave packet can be estimated by assuming that, for each Alfvén wavelength, the electrons are accelerated by the Alfvén wave parallel electric field during a half‐period of the wave. Hess et al [2010, 2011b] showed that in this case, an Alfvén wave packet carrying a power P w transfers to the electrons a power P e given by: where a ( k ) is the phase velocity of a Alfvén wave packet component with a wavenumber k in the equatorial plane (and perpendicular wavenumber ). The electrons to be accelerated are described by a thermal velocity v th and an inertial length λ e .…”
Section: Generation Of Hot Electronsmentioning
confidence: 99%
“…The calculations of Hess et al [2010, 2011b] showed that the transmission function depends mostly on the parallel component of the Alfvén wave vector, whereas the acceleration of the electrons depends only on the perpendicular component. Thus can be re‐written separating the propagation effects which depend on the parallel wavelength () and the electron acceleration itself which depends on the perpendicular wavelength (): The power generate by the Io interaction and put into the Alfvén wave packet ( P w ) varies considerably with time, since Io's orbit and the plasma torus are oriented in different planes, thus introducing a longitudinal modulation of the interaction.…”
Section: Generation Of Hot Electronsmentioning
confidence: 99%
“…When Io is in the center of the torus, the leading spot will overlap with Io's main spot and thus will enhance its brightness as well. A fraction of the wave energy at Io will be partly reflected and filamented while traveling along the inhomogeneous plasma densities and magnetic fields (Wright & Schwartz 1989;Chust et al 2005;Jacobsen et al 2007;Hess et al 2010aHess et al , 2011a. The strength of the wave reflection, transmission and filamentation also depends on Io's position in the torus and will contribute to the variably of the brightness (Hess et al 2013).…”
Section: Poynting Fluxes: Iomentioning
confidence: 99%
“…Zarka (2007) and Hess et al (2011a) estimate values for the energies in the interaction of the satellites with Jupiter's magnetosphere. Our derived values for the Poynting flux are on the same order but somewhat smaller than those in Zarka (2007) since the expressions in Zarka (2007) consider the energy flux into the satellites' ionospheres or the energies dissipated within the satellites' ionospheres, which are generally larger than the energy radiated away from the satellites, which we calculate here.…”
Section: Comparison and Commentsmentioning
confidence: 99%
“…The chosen width corresponds to ∼3 • of latitude, which encompasses the typical day-to-day variability in the main emission location but avoids the selection of significant portions of outer or polar emissions. The longitudinal boundaries of the ROIs correspond to the mapping of boundaries of the equatorial local time sectors at a radial distance of 30 R J using the mapping model from Vogt et al (2015) based on the VIPAL model (Hess et al, 2011). As a consequence, the two ROIs do not cover an equal area on the planet because of the asymmetry of the magnetic field on the surface of the planet.…”
Section: Dawn-dusk Variations In the Main Emission Brightnessmentioning
confidence: 99%